2005
DOI: 10.1038/sj.cgt.7700784
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced inhibition of syngeneic murine tumors by combinatorial therapy with genetically engineered HSV-1 expressing CCL2 and IL-12

Abstract: Herpes simplex viruses type 1 (HSV-1) that lack the g 1 34.5 gene are unable to replicate in the central nervous system (CNS), but maintain replication competence in actively dividing tumors. To determine if antitumor therapy by M002, a g 1 34.5À HSV that Keywords: herpes simplex virus 1; IL-12; CCL2; Neuro-2a; immunohistochemistry E radication of malignancies arising in the brain has proven to be a formidable task. As an example, highgrade malignant gliomas, the most common primary brain tumor, are almost alw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 40 publications
0
53
0
Order By: Relevance
“…26 The group also demonstrated that the virus selected after in vivo serial passage of M002 in tumors of a D54-MG human malignant glioma cell line improved survival in two independent murine brain tumor models compared to the parent M002. 27 This enhanced antitumor efficacy was not due to restoration of protein synthesis or early US11 expression.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…26 The group also demonstrated that the virus selected after in vivo serial passage of M002 in tumors of a D54-MG human malignant glioma cell line improved survival in two independent murine brain tumor models compared to the parent M002. 27 This enhanced antitumor efficacy was not due to restoration of protein synthesis or early US11 expression.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…T cells were stained with CFDA, washed once with T-cell medium and adjusted to 5x10 5 cells/ml in the same medium. An aliquot (100 µl) of the cell suspension containing 5x10 4 T cells was placed in the top chamber of the Transwell. Supernatant obtained from WM3450 or WM35 cell culture or chemokine, prepared at the indicated concentration in T-cell medium (500 µl total volume), was added to the bottom chamber of the Transwell.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] Such studies have provided potent tumor vaccines based on ex vivo transduction of chemokines into tumor cells, inducing tumor rejection mediated by infiltrating T cells at the vaccine site in mice. 1,4 Other approaches, including the fusion of chemokines to tumor Ag-specific antibody to attract adoptively transferred or endogenous T cells to the tumor site, or incorporation of chemokines into Ag vaccines to attract T cells to the vaccine site, have also resulted in tumor destruction in mouse models. 5,6 Development of immunotherapeutic strategies for cancer patients based on chemokines and their receptors awaits a better definition of the role of these molecules in T-cell migration toward tumor cells of patients.…”
Section: Introductionmentioning
confidence: 99%
“…The data were analyzed for statistical significance using a linear mixed model, as described previously. 32 …”
Section: Hsv-1 Expressing CD For Brain Tumor Therapy Mb Guffey Et Almentioning
confidence: 99%